O ÃNDICE DE VARIAÃ‡ÃƒO, UM SUBSTITUTO VANTAJOSO DO COEFICIENTE DE VARIAÃ‡ÃƒO - Gomes, F. Pimentel (REVISTA DE AGRICULTURA, 2015)
O ÃNDICE DE VARIAÃ‡ÃƒO, UM SUBSTITUTO VANTAJOSO DO COEFICIENTE DE VARIAÃ‡ÃƒO